Predicting risk of underconfidence following maternity leave. Issue 11 (14th June 2019) - van Boxel, Elizabeth; Mawson, Isabel; Dawkins, Sarah; Duncan, Sandra; van Boxel, Gijs
Abstract : Objective: To determine what factors affect paediatric trainee confidence on return to work after maternity leave. Design: Information was collected anonymously via an online survey from trainees who had taken maternity leave. Setting: The survey was distributed centrally to each UK deanery. Main outcome measures: Trainee confidence was rated retrospectively using self-assessment. Results: 146 paediatric trainees from 12 out of 13 deaneries completed the survey. 96% of trainees experienced an initial lack of confidence, with 36% requiring 3 months or longer for their confidence to return. Prolonged lack of confidence was associated with longer time out of training, training stage, returning part-time, less frequent engagement with educational activities and lack of recognition by supervising consultant. Conclusion: We propose a scoring system using the above risk factors, the MoTHER score (Months out, Training stage, Hours worked on return, Educational activities, Recognition by consultant), which can be used to identify trainees who are at higher probability of experiencing reduced confidence on return to work.